Integration of two-dimensional transition metal dichalcogenides with Mie-resonant dielectric nanostructures. Issue 1 (1st January 2020) - Mupparapu, Rajeshkumar; Bucher, Tobias; Staude, Isabelle
ABSTRACT: Integrating transition metal dichalcogenide (TMD) monolayers with dielectric nanostructures exhibiting Mie-like resonances opens a plethora of opportunities in manipulating their excitonic emission in the near-field and far-field regimes, yielding interactions spanning from weak to strong coupling regimes, and routing valley polarized chiral emission, to name just a few. Moreover, there is a completely new path unraveled recently by realizing dielectric resonators directly from TMDs, thus combining scatterer and emitter into a single entity. This hybrid configuration is promising to realize integrated active meta-optical devices in a facile manner. In this review article, we provide an overview of the state of the art on integrating monolayers of TMDs with Mie-resonant photonic nanostructures. Graphical Abstract: